Examining equity in a void of evidence - Pharmacist minor ailments services and the role of systematic reviews - Joanna Hikaka; Robert Haua (Elsevier, 2022)
Pharmacist minor ailment services (PMAS) are formalised services which remunerate pharmacists for delivering care and providing medicines used to treat minor ailments such as hayfever, musculoskeletal pain, head lice and constipation. PMAS have been postulated to improve medicines access equity yet there is little evidence to suggest that equitable health outcomes from PMAS have been achieved in those countries where these services have been initiated. Systematic reviews are regarded as the gold standard in assessing evidence of outcome effectiveness, including equity of outcomes. Our research team developed a systematic search strategy and review protocol to examine ethnic variation in PMAS outcomes. No results were returned, even with the inclusion of grey literature, and therefore the impact of PMAS on ethnic equity could not be examined. This commentary discusses the potential for PMAS to achieve medicines access equity and the role of empty reviews in identifying gaps in the literature and advocating for equity.